Hereditary neuropathy with liability to pressure palsies: a single-center experience in southern Brazil - Paulo José Lorenzoni; Cláudia Suemi Kamoi Kay; Cristiane Cavalet; Raquel C. Arndt; Lineu Cesar Werneck; Rosana Herminia Scola (MDPI AG, 2016)
The spectrum of clinical and electrophysiological features in hereditary neuropathy with liability to pressure palsies (HNPP) is broad. We analyze a series of Brazilian patients with HNPP. Correlations between clinical manifestations, laboratory features, electrophysiological analyze, histological and molecular findings were done. In five cases, more than one episode occurred before diagnosis. Median nerve in the carpal tunnel at the wrist, ulnar nerve in its groove at the elbow, fibular nerve in the head of the fibula at the knee, radial nerve in its groove of the humerus and suprascapular nerve in its notch at the supraspinous fossa were found as focal neuropathies. One patient presented with persistent writer's cramp after ulnar nerve palsy. Nerve conduction studies showed focal neuropathy in all patients and concomitant generalized symmetrical neuropathy in eight patients. Molecular analysis of the PMP22 gene detected deletion of the 1.5-Mb fragment in all patients.